Polyphenols-Rich Fruit (Euterpe edulis Mart.) Prevents Peripheral Inflammatory Pathway Activation by the Short-Term High-Fat Diet - Santamarina, Aline Boveto (Molecules, 2019)
Juçara berry is a potential inflammatory modulator, rich in dietary fiber, fatty acids, and anthocyanins. Considering this, we evaluated the high-fat diet (HFD) intake supplemented with different doses of freeze-dried juçara pulp on the TLR4 pathway. Twenty-seven male Wistar rats with ad libitum access to food and water were divided into four experimental groups: control standard chow group (C); high-fat diet control group (HFC); high-fat diet juçara 0.25% group (HFJ0.25%); and high-fat diet juçara 0.5% group (HFJ0.5%). The inflammatory parameters were analyzed by ELISA and Western blotting in liver and retroperitoneal adipose tissue (RET). The HFJ0.25% group had the energy intake, aspartate transaminase (AST) levels, and liver triacylglycerol accumulation reduced; also, the tumor necrosis factor α (TNF-α) and TNF receptor-associated factor 6 (TRAF6) expression in RET were reduced. However, there were no changes in other protein expressions in liver and adipose tissue. Adiposity and pNFκBp50 had a positive correlation in HFC and HFJ0.5%, but not in the C group and HFJ0.25%. The necrosis hepatic score did not change with treatment; however, the serum (AST) levels and the hepatic triacylglycerol were increased in HFC and HFJ0.5%. These results demonstrated that one week of HFD intake triggered pro-inflammatory mechanisms and liver injury. Additionally, 0.25% juçara prevented inflammatory pathway activation, body weight gain, and liver damage